Serum Levels of OPG, RANKL, and RANKL/OPG Ratio in Patients with Ankylosing Spondylitis: A Systematic Review and Meta-analysis. (4th July 2019) - Chen, Mengya; Hu, Xingxing; Wu, Meng; Yang, Jiajia; Han, Renfang; Ma, Yubo; Zhang, Xu; Yuan, Yaping; Liu, Rui; Wang, Mengmeng; Jiang, Guangming; Deng, Jixiang; et al.
ABSTRACT: Objectives : To investigate the role of osteoprotegerin ( OPG ), receptor activator of nuclear factor-kB ligand ( RANKL ), and RANKL/OPG ratio in the pathogenesis of ankylosing spondylitis (AS). Methods : Studies that compared serum levels of OPG, RANKL, and RANKL / OPG ratio between AS patients and healthy controls were gathered. Pooled standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated by the random-effects model. Results : Twenty studies containing 1592 AS patients and 1064 healthy controls were included in this meta-analysis. Serum levels of OPG, RANKL, and RANKL/OPG ratio in AS patients were significantly higher than that in normal controls ( OPG : SMD = 0.401, 95%CI = 0.026–0.777, p = 0.036; RANKL : SMD = 1.116, 95%CI = 0.510–1.723, p < 0.001; RANKL/OPG ratio: SMD = 0.691, 95%CI = 0.084–1.299, p = 0.026, respectively). Subgroup analysis suggested that Asian AS patients and patients with elevated ESR (ESR >20 mm/h) had higher serum OPG levels compared to normal controls. Asian patients, CRP >10 mg/L, ESR >20 mm/h, duration of disease ≤8 years, and BASDAI score >4 points subgroups showed increased RANKL levels compared to controls. Conclusions : Serum levels of OPG, RANKL, and RANKL/OPG ratio may be used as potential susceptible biomarkers for AS, but they could be influenced by race, inflammatory factors, and disease activity of AS patients.